11th AIAA/ISSMO Multidisciplinary Analysis and Optimization Conference 2006
DOI: 10.2514/6.2006-7050
|View full text |Cite
|
Sign up to set email alerts
|

A Nonstationary Covariance Based Kriging Method for Metamodeling in Engineering Design

Abstract: Metamodels are widely used to facilitate the analysis and optimization of engineering systems that involve computationally expensive simulations. Kriging is a metamodeling technique that is well known for its ability to build surrogate models of responses with nonlinear behavior. However, the assumption of a stationary covariance structure underlying Kriging does not hold in situations where the level of smoothness of a response varies significantly. Although nonstationary Gaussian process models have been stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The Treed Gaussian process approach of Gramacy and Lee (2008) can also improve the coverage, because the space can be partitioned into different regions with the response in each region having different variance. Yet another approach to improve the coverage in kriging is to use a nonstationary covariance function (Xiong et al 2007). In a recent work, Gramacy and Lee (2011) showed that the coverage of kriging CIs can be significantly improved by adding a nugget term to the predictor.…”
Section: Confidence Interval For Idwmentioning
confidence: 99%
“…The Treed Gaussian process approach of Gramacy and Lee (2008) can also improve the coverage, because the space can be partitioned into different regions with the response in each region having different variance. Yet another approach to improve the coverage in kriging is to use a nonstationary covariance function (Xiong et al 2007). In a recent work, Gramacy and Lee (2011) showed that the coverage of kriging CIs can be significantly improved by adding a nugget term to the predictor.…”
Section: Confidence Interval For Idwmentioning
confidence: 99%
“…Although a non-stationary correlation function is expected to be more effective for non-linear function approximation (e.g., Ref. 28), it is out of the scope in this study on dynamic adaptive sampling for UQ. Next, consider that the real value of f (ξ) is given at N sample points ξ (1) , ξ (2) , · · · , ξ (N ) .…”
Section: A Fundamentalsmentioning
confidence: 99%
“…Although a non-stationary correlation function is expected to be more effective for non-linear function approximation (e.g., Ref. 11 ), here we focus on the stationary correlation function. Next, consider that the real value of f (ξ) is given at N sample points ξ (1) , ξ (2) , • • • , ξ (N ) .…”
Section: Iia Fundamentalsmentioning
confidence: 99%